Isolation and Characterization of Lactic Acid Bacteria (LAB) With Potential As Probiotics From Shrimp Paste Tanjungbalai Asahan - tahyat, niva; Rasyidah; Ulfayani Mayasari (International Journal of Ecophysiology, 2025)
Terasi or belacan is an example of a fermented product from shrimp that involves lactic acid bacteria. Lactic acid bacteria are a group of gram-positive bacteria that have the ability to produce antagonistic molecules that can be used as antibacterial probiotics and preservatives. This study was conducted to determine the presence of Lactic Acid Bacteria (LAB) which might detect shrimp paste in Tanjungbalai and to the antibacterial activity. This study uses descriptive data analysis, which begins with isolation and characterization by carrying out gram staining and biochemical tests and then continuing with a probiotic potency test which includes a test to acidity (pH) and a test of phatogenic antibacterial activity. Isolations and characterization of LAB produced 6 isolates in the form of coccus, the edges of the colony were whole or flat, the elevation was flat or milky white in color. Meanwhile, the cell morpholgy of 6 LAB isolates was in the form of bacilli, gram positive and monobacillary arrangement. Characterization based on biochemical tests found isolates belonging to the genus Pediococcus, Weisella and Lactobacillus. The results of probiotic tests of 6 isolates were expressed with gastric acid conditions (pH 2.5-3) and had phatogenic antibacterial activity which was marked by the fomation of an inhibition against 2 Escherichia coli test bacteria with the largest inhibition zone size being 8.95 mm while Staphylococcus aureus with the largest inhibition zone size was 12.6 mm. Based on the research that has been done, it can be concluded that LAB from Tanjungbalai shrimp paste has potential as a probiotic because the six isolates obtained met the requirements of bacteria as probiotics, namely being able to withstand acidic conditions and having phatogenic antibacterial activity.